2003
DOI: 10.1128/jvi.77.23.12886-12890.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rat Model of Borna Disease Virus Transmission: Epidemiological Implications

Abstract: Rapid transmission of Borna disease virus occurred upon cohabitation of persistently infected and naive rats. Infectious virus, which was abundantly present in fresh urine samples of carrier rats, entered the brains of recipient rats via the olfactory route. Thus, susceptible farm animals possibly acquire the virus from persistently infected rats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…This may be of particular relevance for the maintenance and spread of BDV during natural infections. It was shown that newborninfected rats start to secrete infectious virus in the urine only approximately 3 months after infection, and it has been proposed that intranasal infection with virus from the urine of persistently infected rodent vectors is the major mode of BDV transmission in the wild (44). These considerations suggest that …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This may be of particular relevance for the maintenance and spread of BDV during natural infections. It was shown that newborninfected rats start to secrete infectious virus in the urine only approximately 3 months after infection, and it has been proposed that intranasal infection with virus from the urine of persistently infected rodent vectors is the major mode of BDV transmission in the wild (44). These considerations suggest that …”
Section: Discussionmentioning
confidence: 96%
“…Immunocompetent rats receiving BDV as adults almost invariably develop severe immune-mediated meningoencephalitis, resulting in massive neuronal destruction throughout the CNS. Adult athymic nude rats and newborn rats infected within the first 24 h of birth, in contrast, fail to mount an efficient cellular immune response and survive BDV infection, resulting in the establishment of life-long viral persistence and secretion of infectious virus in the urine (44). Persistence in newborn-infected rats is associated with distinct pathological changes in defined areas of the CNS.…”
mentioning
confidence: 99%
“…Nonetheless, successful experimental intranasal infection of rats (Carbone et al, 1987;Morales et al, 1988;Stitz et al, 2002), mice, sheep and horses (reviewed by Staeheli et al, 2000) and the presence of BDV antigen or RNA in the olfactory epithelium, nerves and bulb of naturally infected horses point strongly towards an olfactory route, although trigeminal and pharyngeal nerve routes cannot be excluded (Bilzer et al, 1996). Infection most probably occurs via excreta: experimentally chronically infected rats excrete BDV abundantly in urine (and less in tears and saliva; Table 2), and can infect other rats in close contact (Morales et al, 1988;Stitz et al, 1998;Sauder & Staeheli, 2003). In addition to urine, experimentally chronically infected wild bank voles seem to excrete BDV even more commonly in faeces .…”
Section: Diseases Caused By Bdvmentioning
confidence: 99%
“…Thirdly, BDV strains cluster geographically rather than according to the species or year of isolation, suggesting that transmission within a domestic species is uncommon (Kolodziejek et al, 2005). Furthermore, BDV is transmitted in rodents: vertically in mice (Okamoto et al, 2003) and horizontally in rats via urine (Sauder & Staeheli, 2003). Direct evidence of BDV in wild small mammals also exists: BDV or a very closely related virus infects the bicoloured white-toothed shrew (Crocidura leucodon) (Hilbe et al, 2006), bank vole (Myodes glareolus) and root vole (Microtus oeconomus; Kinnunen et al, 2007), and experimental infection of bank voles leads to chronic infection and excretion without major pathology or symptoms .…”
Section: Phylogeny and Molecular Epidemiologymentioning
confidence: 99%
“…Immunohistochemical analysis (10) revealed only a few virus-positive cells in the brains of these animals (data not shown). By contrast, injection of the same dose of recombinant wild-type virus resulted in fulminate virus growth in rat brains (data not shown) and neurological disease within 20 to 21 days postinfection (Table 1).…”
mentioning
confidence: 99%